Respiratory Syncytial Virus, Influenza and SARS-CoV-2 in Homeless People from Urban Shelters: A Systematic Review and Meta-Analysis (2023) - Matteo Riccò; Antonio Baldassarre; Silvia Corrado; Marco Bottazzoli; Federico Marchesi (MDPI AG, 2024)
Homeless people (HP) are disproportionally affected by respiratory disorders, including pneumococcal and mycobacterial infections. On the contrary, more limited evidence has been previously gathered on influenza and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and very little is known about the occurrence of human respiratory syncytial virus (RSV), a common cause of respiratory tract infections among children and the elderly. The present systematic review was designed to collect available evidence about RSV, influenza and SARS-CoV-2 infections in HP, focusing on those from urban homeless shelters. Three medical databases (PubMed, Embase and Scopus) and the preprint repository medRxiv.org were therefore searched for eligible observational studies published up to 30 December 2023, and the collected cases were pooled in a random-effects model. Heterogeneity was assessed using the I2 statistics. Reporting bias was assessed by funnel plots and a regression analysis. Overall, 31 studies were retrieved, and of them, 17 reported on the point prevalence of respiratory pathogens, with pooled estimates of 4.91 cases per 1000 HP (95%CI: 2.46 to 9.80) for RSV, 3.47 per 1000 HP for influenza and 40.21 cases per 1000 HP (95%CI: 14.66 to 105.55) for SARS-CoV-2. Incidence estimates were calculated from 12 studies, and SARS-CoV-2 was characterized by the highest occurrence (9.58 diagnoses per 1000 persons-months, 95%CI: 3.00 to 16.16), followed by influenza (6.07, 95%CI: 0.00 to 15.06) and RSV (1.71, 95%CI: 0.00 to 4.13). Only four studies reported on the outcome of viral infections in HP: the assessed pathogens were associated with a high likelihood of hospitalization, while high rates of recurrence and eventual deaths were reported in cases of RSV infections. In summary, RSV, influenza and SARS-CoV-2 infections were documented in HP from urban shelters, and their potential outcomes stress the importance of specifically tailored preventive strategies.